Diseño del manual de procesos y procedimientos en la microempresa CASA&HOGAR. - Campo, Luis A. (2022)
The main objective of our investigation is to create a manual book about the processes and procedures of the microbusiness known as Casa & Hogar, the investigation took into consideration theoretic fundamentals of a smallbussiness. The manual book has a purpose to improve the business's management indicators, due to this, the applied investigation had a qualitative and quantitative focus, as well as a high level of explanatory and descriptive features. This type of investigation was both a documentary and a field research, the method used to complete said research was deductive with a technical affinity on observations and interviews. The results of this survey allows process surveys to be conducted through BPM:RAD. Substantiating the logical modeling phase, the preliminary design and BPM design. Subsequently, in chapter 3 the critical factors on the key processes of the microbusiness are determined, sustained by the ASS IA, TOBE matrix, with all this the management indicators are resolute and the whole investigation is consolidated into a manual. Finally, conclusion and recommendations are established where the most important conclusion is that in Casa & Hogar the procedures that are developed were not organized, documented nor standardized; this organization presented empirical procedures without a systematization nor qualifications, work processes like: strategic, operative or support.